Petri Net modelling approach for analysing the behaviour of Wnt/β‐catenin and Wnt/Ca2+ signalling pathways in arrhythmogenic right ventricular cardiomyopathy. Issue 6 (23rd November 2020) - Azim, Nazia; Ahmad, Jamil; Iqbal, Nadeem; Siddiqa, Amnah; Majid, Abdul; Ashraf, Javaria; Jalil, Fazal
Abstract : Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited heart muscle disease that may result in arrhythmia, heart failure and sudden death. The hallmark pathological findings are progressive myocyte loss and fibro fatty replacement, with a predilection for the right ventricle. This study focuses on the adipose tissue formation in cardiomyocyte by considering the signal transduction pathways including Wnt/ β ‐catenin and Wnt/Ca 2+ regulation system. These pathways are modelled and analysed using stochastic petri nets (SPN) in order to increase our comprehension of ARVC and in turn its treatment regimen. The Wnt/ β ‐catenin model predicts that the dysregulation or absence of Wnt signalling, inhibition of dishevelled and elevation of glycogen synthase kinase 3 along with casein kinase I are key cytotoxic events resulting in apoptosis. Moreover, the Wnt/Ca 2+ SPN model demonstrates that the Bcl2 gene inhibited by c‐Jun N‐terminal kinase protein in the event of endoplasmic reticulum stress due to action potential and increased amount of intracellular Ca 2 + which recovers the Ca 2 + homeostasis by phospholipase C, this event positively regulates the Bcl2 to suppress the mitochondrial apoptosis which causes ARVC.